MicroRNA-181b is increased in cystic fibrosis cells and impairs lipoxin A4 receptor-dependent mechanisms of inflammation resolution and antimicrobial defense. Issue 1 (December 2017) - Pierdomenico, Anna; Patruno, Sara; Codagnone, Marilina; Simiele, Felice; Mari, Veronica; Plebani, Roberto; Recchiuti, Antonio; Romano, Mario
Abstract The involvement of microRNA (miR) in cystic fibrosis (CF) pathobiology is rapidly emerging. We previously documented that miR-181b controls the expression of the ALX/FPR2 receptor, which is recognized by the endogenous proresolution ligand, lipoxin (LX)A4 . Here, we examined whether the miR-181b-ALX/FPR2 circuit was altered in CF. We examined human airways epithelial cells, normal (16HBE14o-), carrying the ΔF508 mutation (CFBE41o-) or corrected for this mutation (CFBE41o-/CEP-CFTR wt 6.2 kb), as well as monocyte-derived macrophages (MΦs) from CF patients. CFBE41o- cells exhibited higher miR-181b and reduced ALX/FPR2 levels compared to 16HBE14o- and CFBE41o-/CEP-CFTR wt 6.2 kb cells. An anti-mir-181b significantly enhanced ALX/FPR2 expression (+ 60%) as well as LXA4 -induced increase in transepithelial electric resistance (+ 25%) in CFBE41o- cells. MΦs from CF patients also displayed increased miR-181b (+ 100%) and lower ALX/FPR2 levels (− 20%) compared to healthy cells. An anti-mir-181b enhanced ALX/FPR2 expression (+ 40%) and normalized receptor-dependent LXA4 -induced phagocytosis of fluorescent-labeled zymosan particles as well as ofPseudomonas aeruginosa by CF-MΦs. These results provide the first evidence that miR-181b is overexpressed in CF cells, impairing some mechanisms of the ALX/FPR2-dependent pathway of inflammation resolution. Thus, targeting miR-181b may represent a strategy to enhance anti-inflammatory and anti-microbial defense mechanisms in CF.